AN ANALYTICAL STUDY OF PURCHASE SATISFACTION ACROSS BRICK AND MORTAR AND E BUSINESS PLATFORMS AMONG NAGPUR CONSUMERS - Meghe, Vaibhav Vilas; Rahate, Vaishali (International Journal of Research -GRANTHAALAYAH, 2025)
This study looks into Nagpur customers’ satisfaction with their purchases on both physical and online marketplaces. Understanding customer preferences and satisfaction levels across various shopping formats has become essential as a result of the fast evolution of the retail landscape brought about by digitalisation. 200 respondents’ questionnaire-based data was gathered using a descriptive research approach, and the study examines important aspects that affect satisfaction, including price, convenience, customer service, and product variety. The results show that brick-and-mortar establishments are superior in terms of customer engagement and service quality, even while e-business platforms are preferred for convenience. In a competitive market, the study provides retailers with insights to improve customer experience and match plans with consumer expectations.